Категорія автора і читача у світлі художньої комунікації на матеріалі роману «Дванадцять обручів» Юрія Андруховича - Деревецька, А. (Літературознавчі обрії. Праці молодих учених, 2010)
Post-structural Michael Foucault’s consideration and Roland Barthes’s thesis about the death of the author have become a datum-point for an observation of the author’s function in the novel «Twelve circles» by Jurij Andruchovych. In the text discussed the author’s «I» is still disappearing between the lines. From time to time in this eclectic discourse enriched with astonishing digressions, parody and pastiche subject of the utterance is reminding of himself, of his competence and disappears in a moment in the depths of the text assuming the role of scripteur.